Continuous Flow Injection Analysis (CFIA) of Metformin Hydrochloride using Microphotmeter Equipped with 530 and 550nm LED - Shakir, Issam M A; Al-abdli, Basim I; Nafea, Huda M (Al-Nahrain Journal of Science, 2018)
Newly developed spectrophotometric method was used in the present research project for the determination of metformin hydrochloride drug (MTF.HCl), via the complexation of the drug with copper(II). The colored products was measured at 530 nm. The optimization of all chemical and physical parameters for MTF- OH- - Cu(II) system are described. A linear range of 94.04 % for 0.0-100 mM was obtained with a Limit of Detection (L.O.D) 662 ng. The newly developed system was applied for the analysis of pharmaceutical preparation. A comparison was made using paired t-test shows that, the newly developed method can be used as an alternative analytical method for the analysis of metformin hydrochloride (MTF). All this project work was based on on-line determination via Continuous Flow Injection Analysis (C.F.I.A).